2022
DOI: 10.1002/srin.202200295
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement and Microstructure Characterization of 1500 MPa Martensitic Steel

Abstract: The application of ultrahigh‐strength martensitic steel in automotive key parts can achieve automotive lightweight. However, the hydrogen embrittlement sensitivity of ultrahigh‐strength martensitic steel is widely concerned by the industry. This article compares the microstructure and the hydrogen brittleness resistance of two 1500 MPa martensitic steels. The grain boundary, the grain size, the martensitic lath, and the precipitate phase in martensitic steel are analyzed by electron backscatter diffraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[25,26] The modified W-H method was used to calculate the dislocation density of the test steel. [27] ρ ¼ 14.4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] The modified W-H method was used to calculate the dislocation density of the test steel. [27] ρ ¼ 14.4…”
Section: Discussionmentioning
confidence: 99%
“…The modified W–H method was used to calculate the dislocation density of the test steel. [ 27 ] ρ=14.4e2b2$$\rho = 14.4 \frac{e^{2}}{b^{2}}$$where e is the effective microstrain, and b is Burger's vector having a value of 2.48 Å. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the RA as island type is the main microstructural constituent controlling this toughness, which highlights the need for a precise identification of these constituents in the studies dealing with the microstructure-toughness relation [ 22 , 23 ]. In the temperature of ferrite nucleation, the carbons will diffuse in the austenite.…”
Section: Discussionmentioning
confidence: 99%
“…In both steels, the DFS decreased with increasing HD; however, the V-added steel showed higher resistance to HE than the SCM435 steel at the same level of HD. Si et al [184] applied a U-bend test to compare the HE resistance of two 1500 MPa martensitic steels, in which a hydraulic press was used to impose constant pressure downward to form a 180° bend on the samples that were fixed by bolts. The deformed samples were then immersed in 0.5 mol•L −1 HCL solution and time to fracture was recorded to compare the HE resistance of the two samples (Figure 28a-c).…”
Section: Bent Beam Testmentioning
confidence: 99%